Reklameoversættelse - Nielsen, Anne Ellerup (HERMES - Journal of Language and Communication in Business, 1989)
Very few works on translation theory deal with the problems of translating adds and promotional texts. Most writers in this field are translators who focus on the difficulties of translating slogans. K. Reiss is one of the few who has established a typology of adds, but since she doesn’t account for extra-textual features, she implicitly excludes a number of advertising and promotional means from the persuasive text type. I therefore argue in favour of a discourse analytical approach in order to classify texts, as e.g. P. Charaudeau’s semio-linguistic approach.